Answer:

**Answer:**

x=2

**Step-by-step explanation:**

3x=4+2(3-x)

Distribute 2 to 3 and x

3x=4+6-2x

Add 2 to both side of the equal sign and combine 4 and 6

5x=10

divide both sides by 5

x=2

Determine 6th term in the geometric sequence whose first term is 3 and whose common ratio is -4.

Pls help this is very easy

If a 20-foot tree casts a 40-foot shadow, how tall is a tree that casts a 48-foot shadow?

What is the square root of 64y16?o 44O 4yo 8o gy

Please help me i will mark brainliest

Pls help this is very easy

If a 20-foot tree casts a 40-foot shadow, how tall is a tree that casts a 48-foot shadow?

What is the square root of 64y16?o 44O 4yo 8o gy

Please help me i will mark brainliest

Minor point: the quadrilateral is **STWR**, *not STRW*. Vertices are named in order.

The measure of angle T is half the measure of arc WRS. The measure of angle R is half the measure of arc STW. The sum of the measures of the two arcs is the measure of a circle, 360°, so you have

... T + R = (WRS)/2 + (STW)/2

... ... = (WRS + STW)/2

... ... = 360°/2 = 180°

Since the sum of T and R is 180°, they are supplementary.

**Answer: **$0.25

**Step-by-step explanation:**

We are given that the cost of 12 goldfish = $3

To find the cost of one goldfish we use** division operator **and divide the cost of 12 gold fishes by 12.

Then , the cost of one gold fish =

⇒ Cost of 1 gold fish

⇒ Cost of 1 gold fish [Divide numerator and denominator by 3.]

⇒ Cost of 1 gold fish [Simplify by dividing 1 by 4]

**Therefore , the cost of 1 goldfish **= $0.25

**Answer:**

0.25

**Step-by-step explanation:**

X= 7-3y

X has to be on one side

6y+2x =14

2x= 14-6y

X= 7-3y

Now we can plug that into the original equation (check)

6y + 2(7-3y)

6y+ 14-6y

14=14

X= 7-3y

Hope this helps!

$648 is the **total amount** the customer will pay for the 1-year plan

percentage, a relative value indicating **hundredth **parts of any quantity.

Given that a customer enrolled in a 1-year product purchase plan that costs $60 per month.

After 6 months, the customer received a monthly **discount** of 20%.

We need to find the **total **amount the customer will pay for the 1-year plan.

Product Plan = $60 per month

Money he pay for 1 month = $ 60

Money He pay for first 6 month = 6 × 60 = $ 360

after 6 month he receives 20% discount **monthly**,

So, Now he pay for 1 month = 60 - 20% × 60

=60-20/100×60

=60-12=48

Money he pay for last 6 month = 6 × 48 = 288

**Total Money** he pay in a year = 360 + 288 = $ 648

Hence, $648 is the **total amount **the customer will pay for the 1-year plan

To learn more on **Percentage **click:

#SPJ2

**Answer:**

$432

**Step-by-step explanation:**

60*6=360

They paid $360 for the first 6 months.

20%*60=.2*60

0.2*60=12

12*6=72

They paid $72 for the last 6 months.

360+72=432

They paid $432

month?

**Answer:**

Credit cards typically have high interest rates compared to most other types of loans. That means it’s potentially expensive to borrow money with a credit card. When you don’t pay your full credit card balance every month, it’s easy to accumulate boatloads of interest fees quickly.

What is a credit card minimum payment? It’s the minimum amount of money a credit card company is willing to accept each month to keep your account in good standing.

Don’t make the mistake of thinking the minimum due is a “monthly payment” you should be making to pay off your credit card bill. When you only pay the minimum due on your credit card statement, your credit card issuer will make a lot of extra money from you.

**Step-by-step explanation:**

Sequence: 3/4, 3/16, 3/64, 3/256

a8=?

a1=3/4

a2=3/16

a3=3/64

a4=3/256

a2/a1=(3/16)/(3/4)=(3/16)*(4/3)=4/16=1/4

a3/a2=(3/64)/(3/16)=(3/64)*(16/3)=16/64=1/4

a4/a3=(3/256)/(3/64)=(3/256)*(64/3)=64/256=1/4

a2/a1=a3/a2=a4/a3=r=1/4

an=a1*r^(n-1)

an=(3/4)*(1/4)^(n-1)

an=(3/4)*(1)^(n-1)/(4)^(n-1)

an=(3/4)*(1/4^(n-1))

an=(3*1)/[4*4^(n-1)]

an=3/4^(1+n-1)

an=3/4^n

n=8→a8=3/4^8

a8=3/65,536

Answers:

The general term or nth term for the sequence is: an=3/4^n

a8=3/65,536

a8=?

a1=3/4

a2=3/16

a3=3/64

a4=3/256

a2/a1=(3/16)/(3/4)=(3/16)*(4/3)=4/16=1/4

a3/a2=(3/64)/(3/16)=(3/64)*(16/3)=16/64=1/4

a4/a3=(3/256)/(3/64)=(3/256)*(64/3)=64/256=1/4

a2/a1=a3/a2=a4/a3=r=1/4

an=a1*r^(n-1)

an=(3/4)*(1/4)^(n-1)

an=(3/4)*(1)^(n-1)/(4)^(n-1)

an=(3/4)*(1/4^(n-1))

an=(3*1)/[4*4^(n-1)]

an=3/4^(1+n-1)

an=3/4^n

n=8→a8=3/4^8

a8=3/65,536

Answers:

The general term or nth term for the sequence is: an=3/4^n

a8=3/65,536